2017
DOI: 10.1017/s1759078717001052
|View full text |Cite
|
Sign up to set email alerts
|

Completely integrated multilayered weave electro-textile antenna for wearable applications

Abstract: This paper proposes a unique, first of its kind fabrication technique for the making of textile antennas. A novel method that provides scope for automation in textile antenna production is presented here. A completely integrated textile antenna fabrication method that eliminates the tasks of positioning and fastening of the various components of a patch antenna is discussed. The technique employs multilayer weaving for the production of a wearable antenna on a cotton substrate. Silver yarn is used for the cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The table shows that the proposed antenna has smaller dimensions than [15, 20, 23] and lower profile than [8, 15, 20, 23]. In addition, the proposed antenna has better radiation efficiency in FS than [19], better radiation efficiency than [22, 23] and better gain [20, 23] when it is mounted directly on a phantom as a wearable antenna for body-centric communications. However, the proposed antenna has outstanding features as a flexible and waterproof structure to achieving a totally garment integrated antenna as well as simple and low-cost fabrication process.…”
Section: Simulation and Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The table shows that the proposed antenna has smaller dimensions than [15, 20, 23] and lower profile than [8, 15, 20, 23]. In addition, the proposed antenna has better radiation efficiency in FS than [19], better radiation efficiency than [22, 23] and better gain [20, 23] when it is mounted directly on a phantom as a wearable antenna for body-centric communications. However, the proposed antenna has outstanding features as a flexible and waterproof structure to achieving a totally garment integrated antenna as well as simple and low-cost fabrication process.…”
Section: Simulation and Experimental Resultsmentioning
confidence: 99%
“…However, the size of almost all of the wearable antennas with AMC, HIS or EBG is relatively large. In addition, it should be mentioned that many of designs for wearable antennas are proposed for operation at 2.45 GHz [8, 10, 1922] and only a few studies are conducted and reported in the open literature on design and performance of broadband and dual-band wearable antennas [9, 15, 23].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the air gap between conductive thread stitches affects the surface conductivity and antenna performance. A wearable electro-textile multilayer woven patch antenna [7] was fabricated on a cotton substrate to operate at 2.45 GHz. In the weaving process [8], conductive yarns of the patch antenna should be arranged according to the major current flow direction to reduce back lobes and improve the gain.…”
Section: Introductionmentioning
confidence: 99%
“…In [6], a button-shaped wearable antenna was designed that can be attached to clothing. In [7], the multilayer weaving method was used to create a textile antenna made of conductive threads. UWB antennas integrated with the 2.45 GHz frequency band were reported in [8,9] to achieve a high data rate using small transmit power.…”
Section: Introductionmentioning
confidence: 99%